TINJAUAN ATAS KONFLIK PROSEDUR VERIFIKASI PENDAFTARAN MEREK DI DIREKTORAT JENDERAL KEKAYAAN INTELEKTUAL - Morinka, Kara; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Abstract: The occurrence of conflicts in trademark registration verification at the Directorate General of Intellectual Property (DJKI) Indonesia, governed by Law Number 20 of 2016 concerning Trademarks and Geographical Indications, arises from subjectivity in the assessment of trademark similarities, registrations made in bad faith, and a lack of transparency in the verification process. This study focuses on analyzing the principle of due diligence by DJKI in preventing trademark conflicts. The research aims to discuss the optimization of the trademark registration verification process to enhance legal protection for trademark owners. The methodology employed is normative legal research with a legislative approach, involving an examination of Law Number 20 of 2016 and other relevant regulations. This study is expected to contribute to the development of legal science and provide strategic input for DJKI  to improve public services. In conclusion, the application of stricter due diligence principles and transparency in the verification process can minimize conflicts and enhance legal protection for trademark owners in Indonesia.Keywords: Conflict, Trademark Registration, Verification